Evaluation of Tatanen di Bale Atikan-Based Extracurricular Environmental Education Program - Ajat Rukajat; Muhamad Taufik Bintang Kejora; Nurlina Nurlina; Li Kun Mei (Fakultas Keguruan dan Ilmu Pendidikan, Universitas Muhammadiyah kendari, 2025)
This study evaluates the Tatanen extracurricular program at Bale Atikan (TdBA) in Purwakarta elementary schools using the CIPP (Context, Input, Process, Product) evaluation model. The assessment examines program effectiveness, student impact, and resource efficiency through a mixed-method approach. A quantitative survey of 187 teachers from 12 schools was conducted alongside qualitative analysis via interviews, observations, and document studies. The findings indicate that the program aligns with the Merdeka Curriculum and Strengthening the Pancasila Student Profile (P5) and is supported by local regulations. The input aspect scored 4.78 (95.50%), highlighting strong curriculum design, student readiness, and instructor availability, though improvements in teaching materials and infrastructure are needed. The process evaluation yielded a 4.81 (96.11%) score, demonstrating effective project-based learning, though challenges in time management and teacher mentoring persist. In terms of product, TdBA significantly enhances ecological awareness (4.83 or 96.67%), fosters innovation (4.75 or 95.00%), and contributes to environmental preservation (4.88 or 97.50%), averaging 4.82 (96.39%). This study provides a framework for evaluating local wisdom-based programs and offers insights for policymakers to support environmental education and expand similar initiatives in other schools.